When is Participatory Local Environmental Governance Likely to Emerge? A study of collective action in participatory municipal environmental councils in Brazil. (14th March 2014) - van, Frank
ABSTRACT Why is local environmental governance in Brazil shaped through the collective action of many, frequently interacting actors in some municipalities, whilst in others it does not take the form of deliberative and inclusive decision‐making? I address this question by zooming in on Brazil's Conselhos Municipais de Meio Ambiente (participatory municipal environmental councils). Through multivariate logistical regression (n = 5202), I show that a large business community, combined with 'small local government', adds significantly to the likelihood of finding participatory forms of solving environmental problems in a municipality, especially when communities have learned from prior experience with participatory policy‐making in other areas. Through multivariate linear regression (n = 1365), I establish that depth and breadth of participatory environmental governance processes is more likely to increase when, amongst other things, people have previous experience with other types of participatory council, and when there are fewer local government officials per capita. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment